MUTU PENDIDIKAN DAN MUTABA’AH YAUMIYAH DALAM PEMBENTUKAN KARAKTER SISWA - Rahmawati, Rahmawati; Darmayanti, Astuti (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2024)
The country will be seen as progressing through the quality of its human resources resulting from education. This painting aims to get an idea of ​​how teacher behavior and character education can improve the quality of education in Indonesia. Character education aims to improve the quality of implementation and quality of education in schools which leads to achieving the formation of students' complete character and noble morals through daily practices with the mutaba'ah yaumiyah program. The research method used is a qualitative approach with a phenomenological type because it wants to explore the issue of educational quality and its influence on the formation of students' character in schools. The data collection method used is interviews with several informants who the researchers consider to have knowledge related to the phenomena mentioned above, while Observation and analysis of documentary data in the form of several relevant journals, books, and mass media literature were used to strengthen the data that researchers managed to obtain in the field. The research results show that the quality of education in the form of character can improve the quality of graduates who are superior, religious, disciplined, and independent. The results of this research have implications for several groups, such as: 1) for the world of education, such as curriculum development, increasing teacher professionalism, evaluation materials, and strengthening the role of schools. 2) for society, such as improving the quality of human resources, strengthening social values ​​, and preventing social problems. Then implications 3) for students, including student self-development, increasing learning motivation, preparing learning motivation and structuring the future.